Endophytic Fungus from Soursop (Annona Muricata L) and Potential Antibacteria - Noverita Noverita; Nastiti Nastiti; Endang Wahyu Ningsih (Journal of Tropical Biodiversity, 2023)
The aim of this research was to isolate endophytic fungi from different parts of soursop plantations in Cikareo Village, Sukabumi, West Java and to test their antibacterial activity. The researchers obtained six isolates from leaves, stems, and fruits of the soursop plant. These isolates displayed varying growth abilities, with only two (Le-1 and St-2) found to inhibit the growth of Escherichia coli bacteria. Overall, this study highlights the potential of endophytic fungi from soursop plantations as a source of antibacterial agents.